UIN SATU Students' Perception of the Use of Social Media: YouTube as a Means of Improving Speaking and Listening Skills - Anjarwati, Luluk (Metafora: Education, Social Sciences and Humanities Journal, 2024)
Abstract This study aims to determine the perceptions of UIN SATU students towards the use of social media, especially YouTube, as a means of improving speaking and listening skills. This study uses a quantitative approach with survey method to measure the perceptions of UIN SATU students towards the use of YouTube as a learning tool. A 5-point Likert scale was used to assess respondents' perceptions of how much they consider YouTube to be helpful in improving their speaking and listening skills. To ensure that this research instrument is reliable, a Cronbach's Alpha reliability test was conducted, where the expected value is ? 0.70, indicating good internal consistency. The Cronbach's Alpha values for the various aspects measured, such as perceptions of speaking ability (0.82), listening ability (0.85), frequency of YouTube use (0.78), and challenges of the use of YouTube faced (0.73), the results are all above the 0.70, meaning that this instrument is reliable for measuring students' perceptions. Most UIN SATU students have a positive perception of the use of YouTube as a means of improving speaking and listening skills, providing content that helps them improve pronunciation, intonation, and comprehension. YouTube is considered an effective medium for independent language learning, as students can access a wide variety of content at any time. The flexibility in choosing the time and topic of learning makes YouTube an ideal resource for students who want to improve their language skills in a practical way. However, it was also found that they face challenges in filtering irrelevant content and maintaining consistency in using YouTube for learning.